Fiscal Deficits, Monetary Reform, and Inflation Stabilization in Romania - Budina, Nina (The World Bank, 2000)
March 2000 - Fiscal problems are a key factor behind the inflation that has persisted in Eastern Europe since 1989. Deficits need to be cut back, but by how much for a given inflation target? A simple framework links debt, the deficit, and inflation to assess the fiscal stance of the Romanian economy. Unsustainable fiscal deficits were the chief reason for the inflation that has persisted in Eastern Europe since 1989. Deficits need to be cut back, but by how much for a given inflation target? Budina and van Wijnbergen develop a simple framework for debt, the deficit, and inflation to study the interactions between fiscal and monetary policy in Romania's economy. This framework can be used to 1) determine the financeable deficit and the required deficit reduction for a given rate of output growth, inflation rate, and target for debt-output ratios, and 2) to find the inflation rate for which no fiscal adjustment is needed. They use this framework to assess consistency between inflation, monetary reform, and fiscal policy in Romania. Many of the issues in Romania are similar to those in other countries. But Romania is an interesting case because of its history of unsuccessful stabilization attempts. The authors' results suggest that fiscal problems during 1992-94 were masked by shifting government expenses to the books of the National Bank of Romania so that the government deficit did not fully reflect public spending. In addition, the effects of delayed fiscal adjustment were mitigated by exchange rate overvaluation and favorable debt dynamics. In the late 1990s, however, debt dynamics worsened and the economy experienced significant real depreciation. That exacerbated the fiscal problems and increased the fiscal adjustment needed to restore consistency.